Determinants of Islamic stock market in Malaysia - Azman, Nurul Shafiqah (2019)
Islamic Finance consists of banking sectors, insurance institutions and listed securities markets. Islamic finance is aims to comply with the central tenets of shariah or Islamic law. Since its beginning four decades ago, the number of Islamic Financial Institutions has increase worldwide from one bank, starting with the Dubai Islamic bank in 1975 and today over 375 banks (Abdul Rehman, 2016). Islamic finance has the ability to meet financing and banking need for Muslims but also for non-Muslims in different nations. On the empirical studies, Islamic stock market has established and operating within the global context also competes against conventional markets. Islamic stock market is a medium for investors to prevent the inflation threats as an indicator of domestic economic development. The investor believes that investing in stock markets can get more advantages and prospective growth in the future plus a lower risk with a strong return relative to conventional stock market. According to Khan, Sulaiman and Farooq (2013), Islamic stock market rules must be free from interest, uncertainty and gambling. Moreover, stock price also may give some impacts.